2000
DOI: 10.1002/(sici)1521-4095(200003)12:5<375::aid-adma375>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Flux Pinning in Bulk Melt Textured 1-2-3 Superconductors: Bringing Dislocations under Control

Abstract: Structural defects are important in type II superconductors since they are responsible for their supercurrent carrying capacity; however, the engineering of defects has been problematic. This report summarizes the difficulties involved and presents recent results dealing with alternative processing routes, such as high oxygen pressure processing, which gives rise to a higher density of partial dislocations (see Figure) and significantly enhanced critical currents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…1 The peritectic reaction is slow, so a fraction of non-reacted peritectic Y-211 can be retained in the final product in the form of inclusions with a size lower than few micrometers. 2 The crystal of YBCO is highly anisotropic, as dislocations are confined to the (0 0 1) plane. Ledbetter et al 3 reported that strong covalent and ionic bonds create high Peierls' barriers which constrain the dislocation mobility in YBCO single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…1 The peritectic reaction is slow, so a fraction of non-reacted peritectic Y-211 can be retained in the final product in the form of inclusions with a size lower than few micrometers. 2 The crystal of YBCO is highly anisotropic, as dislocations are confined to the (0 0 1) plane. Ledbetter et al 3 reported that strong covalent and ionic bonds create high Peierls' barriers which constrain the dislocation mobility in YBCO single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, dislocations in complex oxides are known to exhibit distinct electrical properties compared to the host material (Szot et al, 2006). Although the control of their density and distribution has been extensively studied in other functional oxides in bulk form (Sandiumenge et al, 2000), the spontaneous formation of regular patterns at interfaces in heteroepitaxial systems offers unique opportunities for miniaturization.…”
Section: Misfit Strainmentioning
confidence: 99%
“…This fact could be due to different reasons: (i) Y-211 phase ionic bond is stronger than Y-123 (related to the different melting point of the two different phases: T Y-123 ∼ 1010 • C and T Y-211 ∼ 1200 • C 202 ), and/or (ii) the high anisotropy confined onto the (0 0 1) plane of the Y-211 phase creates dislocations and residual stresses inside the particle due to its compressive state during the solidification process, which generates microcracks in the surrounding matrix. 203 These microcracks drastically affect the microstructure acting as nucleation sites. 203 When the YBaCuO samples textured by self-flux technique are doped with Ca and Sr, E value drastically decreases due to the ionic and crystallographic radius of the different doping elements.…”
Section: Examples Of Elastic Deformation Using Nanoindentationmentioning
confidence: 99%